Occurrence of castor diseases in Tamil Nadu and screening of castor parental lines for wilt resistance: Occurrence of castor diseases in Tamil Nadu and screening of castor parental lines for wilt resistance - V RAVICHANDRAN; N INDRA; P A SARAVANAN; P VEERAMANI; P ARUTCHENTHIL; S R VENKATACHALAM; S MANICKAM (Journal of Oilseeds Research, 2023)
Castor is an important industrial oilseed crop. The survey conducted during 2021-2022 in castor growing area of Tamil Nadu indicated that wilt and gray mold are the major disease. The wilt disease incidence ranged from 10.2 to 25.4 per cent and gray mold disease severity ranged from 37.8 to 62.2 PDI. The screening of castor parental line for wilt resistance in wilt epiphytic condition revealed BCS 3, ICS 253, ICS 309 and IPC 46 found promising for wilt resistance and they can be utilized for the development of wilt resistant castor hybrids.